2020
DOI: 10.3390/jfb11020032
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Quantification of the Distribution of CN-NL Nanoparticles Encapsulating Glycyrrhetic Acid on Novel Textile Surfaces with Hyperspectral Imaging

Abstract: Chitin Lignin nanoparticles (CN-NL), standalone and encapsulating glycyrrhetic acid (GA), were applied on novel substrates for textiles to obtain antibacterial, antioxidant properties. Their homogeneous application is an important parameter that can strongly influence the final performance of the investigated textiles for its cosmetic and medical use. In this paper, hyperspectral imaging techniques combined with chemometric tools were investigated to study the distribution and quantification of CN-NL/GA on chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In fact, on the nanoscale, chitin is able to modulate the pro- and anti-inflammatory reaction of dermal keratinocytes [ 1 , 25 ]. The application of an easy and efficient method for decorating the biomaterial surfaces with such components and for quality control of the outcomes has been the subject of recent studies [ 26 ]. Water-based spray of CNs may affect the cellulose substrate surface by wetting.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, on the nanoscale, chitin is able to modulate the pro- and anti-inflammatory reaction of dermal keratinocytes [ 1 , 25 ]. The application of an easy and efficient method for decorating the biomaterial surfaces with such components and for quality control of the outcomes has been the subject of recent studies [ 26 ]. Water-based spray of CNs may affect the cellulose substrate surface by wetting.…”
Section: Discussionmentioning
confidence: 99%
“…CNs and CLA complexes are bio-based nano- and micro-compounds that can be considered useful bioactive agents for functionalizing skin contact substrates, as they showed proficient interaction in an in vitro skin model [ 14 ]. It is important to obtain an easy and effective method for applying such components to biomaterial surfaces to put in contact with skin, encompassing bulk incorporation and surface functionalization [ 15 , 28 ]. In fact, if plain CNs are applied as water suspension, further steps like evaporation must be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Such complexes have demonstrated the ability to incorporate biomolecules such as the glycyrrhetinic acid (GA), which is derived from the licorice plant and possesses anti-inflammatory and antimicrobial properties that are interesting for treating skin disorders [ 13 ]. CN-NL/GA (CLA) complexes were developed by spray dry technology in previous studies and showed promise for skin contact applications, as CN-NL provides a suitable carrier to promote GA delivery [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore chitin, when used at nano dimension, encourages the skin regeneration activity probably because its nanofibrils provide a three-dimensional structure that mimics the natural extracellular matrix (ECM) (Figure 7) [90]. Moreover and first of all, the different polymers and active ingredients have to be well selected, according to their therapeutic or cosmetic applications (Figure 8) [91,92]. Just as an example, our research group has encapsulated glycyrrhetinic acid (GA) as antiinflammatory agent and vitamin E as antioxidant compound into the complex chitin nanofibrils and nanolignin (CN-LG), verifying their distribution on the novel textile surface and the Vit E recovery (Figure 9) [93,94].…”
Section: Biofunctional Textiles and Nanocomposites For Medical And Cosmetic Usementioning
confidence: 99%